2021
DOI: 10.1088/1742-6596/1889/3/032037
|View full text |Cite
|
Sign up to set email alerts
|

Methods for monitoring metrological characteristics of scientific and physical parameters of intelligent sensors in real operating conditions

Abstract: Intelligent sensors - the direction of studying the characteristics of scientific and physical parameters in real conditions (in the regions of Uzbekistan at the Aral Sea). This article provides brief information on monitoring methods using software, an analysis of the physical activity of various sensors in an area of over 220 hectares given in the Khorezm region. Creating a common relationship between humanity and the environment with the support of information technologies.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 12 publications
(5 citation statements)
references
References 0 publications
0
2
0
Order By: Relevance
“…A strong positive correlation r=0.9296 was observed between kinematic viscosity and density values. As a result of the application of the method of least squares, it is shown that the relationship between temperature and kinematic viscosity is connected by a linear function (Figures 10,11). Metrological traceability of the set viscosity value to the primary standard is ensured, the kinematic viscosity of pure water at 20 °C (ITS-90) η=(1.0034±0.17) % [29][30][31].…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…A strong positive correlation r=0.9296 was observed between kinematic viscosity and density values. As a result of the application of the method of least squares, it is shown that the relationship between temperature and kinematic viscosity is connected by a linear function (Figures 10,11). Metrological traceability of the set viscosity value to the primary standard is ensured, the kinematic viscosity of pure water at 20 °C (ITS-90) η=(1.0034±0.17) % [29][30][31].…”
Section: Resultsmentioning
confidence: 99%
“…Uzbekistan is a member of the COMET regional metrology organization. One of the main quality and safety indicators is kinematic viscosity [9][10][11][12][13][14][15].…”
Section: Main Partmentioning
confidence: 99%
“…Currently, according to clause 6.5 of the ISO/IEC 17025:2017 [7,15,16] standard, metrological traceability of the results of measurements carried out in laboratories should be ensured. Accordingly, it is necessary to calibrate the measurements performed in laboratory conditions and to assess the uncertainty of the measurement results.…”
Section: Methodsmentioning
confidence: 99%
“…The basis of the principle of action of capacitive-semiconductor converter of dispersed media humidity is the dependence between the humidity of the measured mediumW and its electro-physical properties, the change in the active and reactive resistance of the transducers depending on the dielectric constant of the wet medium [4][5][6]. The essence of the method is to determine the permittivity of the medium by measuring the active and reactive resistance and energy losses of the electric capacitor, in which the role of the dielectric is played by the media [7][8][9][10].…”
Section: Introductionmentioning
confidence: 99%
“…Graph models of the distributed circuit of the capacitive-semiconductor converter are reduced to the transition from complex differential and integral equations to the discretization of algebraic relations, describing and displaying unknown values of the quantities that are the nodal element in the distributed circuit of the converter [7][8][9]. When studying and displaying the transformation circuit of the probe capacitance-semiconductor converter based on the graph model, this circuit is conditionally divided into elementary sections х ' , consisting of input and output quantities and parameters, which, in turn, are exposed to external influences of quantities of different physical nature.…”
Section: Introductionmentioning
confidence: 99%